Planning for learning - McLeod, Julie Hinde (Thomson/Social Science Press, 2003)
This book represents the next step in the critical role that lesson planning plays in effective teaching. The authors examine practices from many different areas of education in the U.S. and around the world to create an approach to lesson planning and evaluation that will work in today's diverse school settings. The heart of the book demonstrates collaborative lesson planning for teachers at particular career phases-pre-service, novice, and experienced.